Homicidal ideation and psychiatric comorbidities in the inpatient adolescents aged 12–17 - Sun, Ching-Fang; Mansuri, Zeeshan; Trivedi, Chintan; Vadukapuram, Ramu; Reddy, Abhishek (Frontiers in Psychiatry, 2022)
Objectives: Adolescents with homicidal tendency is a growing concern in the United States. Studies in the past have showcased the relationship between homicidal ideation (HI) and psychiatric illnesses, but very limited information is available on the adolescent and inpatient population. We aim to evaluate the prevalence of demographic characteristics and psychiatric disorders in adolescents with and without HI. Methods: Adolescent (age 12-17) population admitted to the hospital with the diagnosis of homicidal ideation were identified from the 2016-2018 National Inpatient Sample Dataset (NISD). Patients without HI were defined the control group. The prevalence of psychiatric comorbidities between the groups was compared by applying the Rao-Scott adjusted Chi-Square test. Multivariable logistic regression as applied to generate odd ratio (OR) of homicidal ideation as an outcome; we adjusted age, sex, race, socioeconomic status, substance use disorders, alcohol use disorders and psychiatric comorbidities. Results: A total of 18935 patients (mean age: 14.5) with HI diagnosis were identified in this study. Majority of the patients were male in the HI group compared to the control group (58.7% vs. 41.2%, p < 0.001). Racially, HI was more prevalent in white race (56.0% vs. 52.6%, p < 0.001) and black race (22.3% vs. 17.8%, p < 0.001), compared to Hispanic race (14.9% vs. 21.3%, p < 0.001). Major depression (Odds ratio [OR]:2.66, p<0.001), bipolar disorder (OR:3.52, p<0.001), anxiety disorder (OR:1.85, p <0.001), ADHD and other conduct disorders (OR: 4.01, p<0.001), schizophrenia (OR:4.35, p<0.001) are strong predictors of HI. Suicidality was prevalent in 66.9% patients with HI. Conclusions: We found a higher prevalence of psychiatric illnesses such as depression, anxiety, and bipolar disorder in adolescents with homicidal ideation in inpatient setting. White and black races were more prevalent in patients with homicidal ideation. Further large-scaled longitudinal research studies are warranted to establish the correlation between psychiatric disorders and homicidal ideation among adolescents.